Nilai Pendidikan Tattwa Pada Tutur Parakriya - I Wayan Arya Adnyana (Jayapangus Press, 2020)
This study aims to: increase a deeper understanding of the value of tattwa education in Tutur Parakriya. This data is obtained using a method, and this method must also be precise so that the data obtained can be accurate and support the research results. This type of research is qualitative because it is a text research or library research whose primary data source is Tutur Parakriya which has been transcribed into text / text form. Literature study and interviews are used as data collection methods and then descriptive qualitative data processing is performed. As far as researchers know, no one has researched about this papyrus, so it is only based on text / text transcripts. This research uses the concept foundation to describe the problems to be discussed, and as a scalpel uses the theory of meaning and hermeneutic theory. The results of Tutur Parakriya's research contain the value of tattwa education, that is advice or advice to teach Hindus to be able to get the perfection of birth and mind.